Interfacial Synthesis of Nylon‐6, 6 and Its Modification with Silver‐Based Nanoparticles at the Electrified Liquid‐Liquid Interface. Issue 18 (23rd August 2022) - Kowalewska, Karolina; Sipa, Karolina; Kaczmarek, Katarzyna; Skrzypek, Sławomira; Poltorak, Lukasz
Abstract: In this work, the synthesis of Nylon‐6.6 together with silver nanoparticles (presumably Ag2 O, Ag NPs) was carried out at a polarized liquid‐liquid interface (LLI). The reduction of silver ions to Ag‐NPs was driven by an electrochemically controlled electron transfer reaction between silver cations initially dissolved in the aqueous phase and ferrocene species present in the organic phase. The formation of Ag2 O is assumed to originate from Ag + precipitation to AgOH further converted into Ag2 O. The polyamide formation was derived from the interfacial polycondensation reaction happening between 1, 6‐diaminohexane and adipoyl chloride. We studied the possibility to form given material simultaneously (interfacial polycondensation and Ag + reduction occurring in one step) and sequentially (electrochemical Ag + reduction by ferrocene from the organic phase was performed after polyamide deposition). The Ag‐based NPs‐polyamide material was synthesized at the macroscopic and microscopic LLI. As the support for the latter, fiberglass membranes was used. The resulting material was characterized by infra‐red (IR) spectroscopy and scanning electron microscopy (SEM). Abstract : Electrifying : The electrified liquid‐liquid interface was simultaneously modified with polyamide (Nylon‐6, 6) and silver based particles under electrochemical control. Silver was dissolved in the aqueous phase together with 1, 6‐diaminohexane (soluble complex is formed), whereas the organic phase was the solution of adipoyl chloride and ferrocene.